Islamic Values as Contrastive Analysis for Teaching Reading: ELT in Islamic Higher Educational Institution - Shahibul Muttaqien Al-Manduriy (Universitas Al-Qolam Malang, 2026)
This study explores the integration of Islamic values in English Language Teaching especially reading within Islamic higher educational institutions, utilizing contrastive analysis as a pedagogical approach. The integration of these values aims to create a learning environment that not only emphasizes language skills but also reinforces Islamic ethical and moral principles. Contrastive analysis, which compares the students' native language (L1) with English (L2), helps educators identify potential challenges and similarities, facilitating a more effective and contextually relevant language acquisition process. This method allows instructors to design reading challenges and activities to improve reading skills while infusing Islamic perspectives. In teaching generic text structures, contrastive analysis enables a comparison of Arabic language awareness with English terminology, assisting students in mastering these structures with an understanding of both linguistic contexts. Furthermore, contrastive analysis supports vocabulary acquisition by connecting English words with Islamic concepts, enhancing students' cultural sensitivity and ethical engagement with language learning. By linking English terminology with Islamic principles such as